Clean rhodium nanoparticles prepared by laser ablation in liquid for high performance electrocatalysis of the hydrogen evolution reaction. Issue 11 (24th October 2019) - Volpato, Giulia Alice; Muneton Arboleda, David; Brandiele, Riccardo; Carraro, Francesco; Sartori, Giovanni Battista; Cardelli, Andrea; Badocco, Denis; Pastore, Paolo; Agnoli, Stefano; Durante, Christian; Amendola, Vincenzo; Sartorel, Andrea
Abstract : Rhodium nanoparticles prepared by a facile laser ablation procedure show excellent activity towards the hydrogen evolution reaction. Abstract : Rhodium nanoparticles (NPs) were prepared by a one-step, green and facile procedure consisting in laser ablation of a bulk Rh target immersed in pure water (W–Rh-NPs) or ethanol (E–Rh-NPs). When embedded in mesoporous carbon based inks, both W–Rh-NPs and E–Rh-NPs show excellent activity towards the hydrogen evolution reaction in acidic media, operating close to the thermodynamic potential with 85–97% faradaic yields and low Tafel slopes of 50–54 mV per decade in the low overpotential region ( η < 20 mV). A superior activity of W–Rh-NPs with respect to E–Rh-NPs is ascribed to the absence of surface carbon reducible species derived from the synthesis in organic solvent, and thus confirms the importance of the use of water as the preferred medium for laser synthesis of clean nanocrystals in liquid environment. These results provide an important contribution to the impelling need for the preparation of nano-catalysts based on energy critical materials by clean, sustainable and low cost routes.